Design of monitoring information system FTTH (fiber to the home) CV. Fastnet media web-based - Wawan Septiana; Edy Supriyanto (Institute of Computer Science (IOCS), 2023)
Developments in making customer-oriented services (customer oriented) are numerous so that they are increasingly spoiling customers. Likewise with the very rapid development of the Start Up world in Indonesia, so that many large companies are interested in developing Start Ups under their supervision, such as CV Fasnet Media collaborating customer oriented and Start Up services. Collaboration is carried out such as in building a system to prevent interruptions in products and subscriptions. In the course of the New interruption and subscription prevention system requires a website to monitor the operation of the system. CV Fasnet Media is still experiencing bandwidth management problems, therefore a special system is needed where workers can more easily manage data -data l to support the administration of activities that are effective, efficient and can provide easily accessible information facilities. In monitoring the website, it is intended for the responsible party (Team Leader) in monitoring activation by technicians who use a disturbance prevention system and new subscriptions. In monitoring the website also displays potential fault points around the area, then can manage data technicians and customers registered in the intrusion prevention system. This monitoring makes it easier for Team Leaders because they can manage technicians and see potential interference points visually provided on the web-based Monitoring System website.